CDC25C as a Predictive Biomarker for Immune Checkpoint Inhibitors in Patients With Lung Adenocarcinoma - Zhang, Wengang; Shang, Xiaoling; Yang, Fei; Han, Wenfei; Xia, Handai; Liu, Ni; Liu, Yanguo; Wang, Xiuwen (Frontiers in Oncology, 2022)
The application of immune checkpoint inhibitors (ICIs) in non-small cell lung cancer has significantly improved patient survival. However, most patients fail to respond to ICIs or develop drug resistance during treatment. Therefore, novel biomarkers are needed to predict the efficacy of ICIs or provide clues on how to overcome drug resistance. Here, it was revealed that Cell Division Cycle 25C (CDC25C) expression was upregulated in lung adenocarcinoma (LUAD) compared to that of normal lung tissue in multiple databases. This was further verified by q-PCR. Furthermore, higher CDC25C expression was associated with shorter overall survival and worse pathological stage. Most importantly, a higher CDC25C expression was associated with a shorter progression-free survival in LUAD patients treated with nivolumab, suggesting the role of the cell cycle in immunotherapy. In addition, CDC25C expression was significantly associated with immune cell infiltration in the LUAD tumor microenvironment. Moreover, CDC25C was differentially expressed and correlated with overall survival in multiple tumors, indicating that CDC25C is a broad-spectrum biomarker. Taken together, our study demonstrates that CDC25C is a prognostic biomarker for LUAD patients, especially for patients treated with ICIs. Our study also provides strong evidence for the role of the cell cycle in ICIs therapy and tumor microenvironment.